PENGARUH AKTUATOR PADA AUTOMATISASI RANCANG BANGUN ALAT MUSIK TRADISIONAL BERBASIS MIKROKONTROLER - Wijaya, Indra Trisna; Hadianto, Rahmadani (Jurnal Mahasiswa Terapan, 2026)
This study examines the influence of using solenoid door lock actuators and TCRT5000 reflective sensors in an automatic angklung System based on the Arduino Mega 2560 microcontroller, developed to play 16 notes. The main objective of the research is to design, implement, and evaluate the control performance and sound quality of a traditional musical instrument that can operate automatically, while addressing the limitations in the number of notes and detection accuracy found in previous studies. The methods employed include a literature review, observation of the existing System, and performance testing on 16 notes by measuring response precision of ≤ 50 ms per note and cycle reliability of ≥ 100 repetitions. The test results show that increasing the number of notes from 8 to 16 successfully expanded the melodic range without reducing accuracy. The TCRT5000 sensor provided stable detection of the solenoid plunger position, while the Arduino Mega 2560 was able to process the sequence of strikes accurately. The integration of Arduino, the L298N Driver, solenoid door locks, and the TCRT5000 sensor formed a feedback control loop that ensured precise and consistent striking timing, making this System a viable modern alternative for the preservation and education of traditional music.